Dampak Kegiatan Pariwisata Olahraga Internasional Tour de Linggarjati terhadap Kepariwisataan Kabupaten Kuningan - Muhammad Irfan Dzikrirazak; Taufik Taufik; Agus Herlambang (TRANSBORDERS: International Relations Journal, 2018)
Currently the visiting various interesting places around the world both in business and travel matters is become a global trend. The Indonesian government is aggressively promoting various superior destinations in Indonesia, including sports tourism. This is because of the domino effect of regional tourism development; is the improvement of the people's economy, and of course foreign exchange for the country. Some regions also competed to develop Sports Tourism, including Kuningan regency with the implementation of Tour de Linggarjati. This article seeks to highlight the success of Tour de Linggarjati and its significant impact on Kuningan district.